Weinberg, G. (2020). Escritos sobre el libro y la edición en América Latina. Buenos Aires: CLACSO, UNIPE - Maggio-Ramírez, Matías (2021)
Reseña crítica de Escritos sobre el libro y la edición en América Latina de Gregorio Weinberg.